The Influence of the Learning Environment in Shaping Early Childhood Learning Motivation - Oktaviana, Yogi; Azzahra, Rizqina; Saadah, Siti (Jurusan Pendidikan Islam Anak Usia Dini, 2025)
Early childhood learning motivation is the most important development in learning aspect motivation. The learning environment greatly influences the learning process, which must create a conducive and supportive environment, because it significantly affects early childhood learning motivation. Early childhood learning motivation is influenced by various factors, which include parental support, teacher quality, and adequate facilities. Therefore, early childhood learning motivation must be created, because it greatly affects their enthusiasm for learning. The purpose of this paper is to analyze the effect of learning environment on early childhood learning motivation, with several factors considered. This study found that the interaction between parents and children, teachers and children, friends and children greatly influences early childhood learning motivation. This research has significant implications for developing appropriate learning strategies, thus providing high learning motivation for early childhood. The research method used is the literature method with journal and observation collection techniques. Which from the results of this study strongly proves that the learning environment and motivation for early childhood is very influential on themselves for the next level